Case Report: Tezepelumab as rescue therapy in near-fatal asthma requiring extracorporeal membrane oxygenation - Oruqaj, Gani; Bewersdorff, Johannes; Litzlbauer, Detlef; Wolff, Matthias; Sander, Michael; Seeger, Werner; Grimminger, Friedrich; Hecker, Matthias; Tello, Khodr; Vadász, István (Frontiers in Immunology, 2026)
BackgroundTezepelumab, an anti-thymic stromal lymphopoietin (TSLP) monoclonal antibody, reduces exacerbations across asthma phenotypes, but its role in status asthmaticus and near-fatal exacerbations requiring veno-venous extracorporeal membrane oxygenation (VV-ECMO) is unclear.Methods and ResultsWe report three patients (17, 22, 57 years) with therapy-refractory hypercapnic respiratory failure initiated on VV-ECMO who received tezepelumab 210 mg within 24 h. Tidal volume and minute ventilation increased within 24–72 h, permitting decannulation by days 12–15 and ventilator weaning by days 17–28. Two patients had elevated IgE; one had normal blood eosinophils/IgE. No immediate drug-related adverse events occurred. Follow-up demonstrated lung-function recovery; one patient required escalation of maintenance therapy for persistent symptoms.ConclusionIn this small series, adjunctive tezepelumab during VV-ECMO–supported status asthmaticus appeared safe and potentially beneficial adjunctive therapy during near-fatal asthma requiring VV-ECMO. Randomized controlled studies are needed to determine the impact of TSLP inhibition on recovery time, ventilation duration, and mortality in this setting.